Розвинення функцій за системою поліномів, біортогональних на замкненому контурі з системою регулярних у нескінченно віддаленій точці функцій - Сухорольський, М.А. (Український математичний журнал, 2010)
Исследуются свойства систем полиномов, построенных по аналогичным с полиномами Бериулли и Эйлера схемам. Сформулированы условия существования ассоциированных с полиномами функций, условия представления полиномов контурными интегралами и приведены классы аналитических функций, разлагаемых в ряды по системам полиномов. Разложения функций проиллюстрированы примерами. We study properties of the systems of polynomials constructed according to the schemes similar to the schemes used for the Bernoulli and Euler polynomials, formulate conditions for the existence of functions associated with polynomials and conditions of representation of polynomials by contour integrals, and present the classes of analytic functions expandable in series in the systems of polynomials. The expansions of functions are illustrated by examples.